Building user trust in the digital society: The influence of perceived data security on the DANA digital wallet application - Jenny Karunia Putri Zai; Darwis Robinson Manalu (PT Bina Perfidia Akademia, 2026)
The rapid adoption of digital wallets within society has intensified concerns regarding data security. However, previous studies examining the influence of perceived data security on user trust have primarily focused on statistical relationships without explaining the conceptual mechanism underlying trust formation. This study aims to examine the influence of perceived data security on user trust in the DANA digital wallet application. A quantitative approach employing simple linear regression was conducted using questionnaire data collected from 75 DANA users at Methodist University of Indonesia through a five-point Likert scale. The findings reveal that perceived data security has a positive and statistically significant effect on user trust (R² = 0.738; t = 14.343; p < 0.001), indicating that stronger perceptions of data security lead to higher levels of user trust in digital financial services. This study contributes by proposing a conceptual framework that explains the trust formation process while providing practical recommendations for digital wallet providers to strengthen security systems and enhance public trust in digital transactions. Abstrak Pesatnya penggunaan dompet digital di masyarakat meningkatkan kebutuhan akan keamanan data, namun penelitian mengenai pengaruh persepsi keamanan data terhadap kepercayaan pengguna masih terbatas pada hubungan statistik dan belum menjelaskan mekanisme konseptual pembentukan kepercayaan. Penelitian ini bertujuan menganalisis pengaruh persepsi keamanan data terhadap kepercayaan pengguna aplikasi DANA. Penelitian ini menggunakan pendekatan kuantitatif dengan analisis regresi linear sederhana terhadap 75 mahasiswa pengguna DANA di Universitas Methodist Indonesia melalui kuesioner berbasis skala Likert. Hasil penelitian menunjukkan bahwa persepsi keamanan data berpengaruh positif dan signifikan terhadap kepercayaan pengguna (R² = 0,738; t = 14,343; p < 0,001), yang mengindikasikan bahwa semakin tinggi persepsi keamanan, semakin tinggi pula tingkat kepercayaan pengguna dalam memanfaatkan layanan keuangan digital. Penelitian ini berkontribusi dengan menawarkan kerangka konseptual yang menjelaskan proses pembentukan kepercayaan pengguna serta memberikan rekomendasi bagi penyedia layanan untuk memperkuat keamanan sistem dan meningkatkan kepercayaan masyarakat terhadap transaksi digital.